Lessons from the High-resolution Spectroscopy of AW UMa and ϵ CrA: Is the Lucy Model Valid? - Slavek M. Rucinski (The Astronomical Journal)
A re-examination of high-resolution spectral monitoring of the W UMa–type binaries AW UMa and ϵ CrA casts doubt on the widely utilized L. B. Lucy model of contact binaries. The detection of the very faint profile of the secondary component in AW UMa leads to a new spectroscopic determination of the mass ratio, q _sp  = 0.092 ± 0.007, which is close to the previous, medium-resolution spectroscopic result of T. Pribulla & S. M. Rucinski, q _sp  = 0.101 ± 0.006, and remains substantially different from a cluster of generally accepted photometric results by several authors, concentrated around q _ph  = 0.080 ± 0.005. A survey of binaries with the best-determined values of the mass ratio shows a common tendency for q _ph  <  q _sp . The tendency for systematically smaller values of q _ph may result from the overfilling of the primary lobe and underfilling of the secondary lobe relative to the Roche model geometry, as predicted by the K. Stȩpień model. Despite the observed moderate inter-systemic velocities, the photometric Lucy model may remain useful in providing approximate, though biased, results for the mass ratio. A complicating factor in detailed spectral analysis may be the occurrence of Enhanced Spectral-line Perturbations (ESPs) projected over the secondary profiles, appearing in different numbers in the two studied binaries. The ESPs are tentatively identified within the Stȩpień model as collision fronts or fountains of primary-component gas from the circumbinary, energy-carrying flow.